Eyelid fat grafting: Indications, operative technique and complications; a systematic review. Issue 4 (April 2016) - Boureaux, Elodie; Chaput, Benoit; Bannani, Sahar; Herlin, Christian; De Runz, Antoine; Carloni, Raphael; Mortemousque, Bruno; Mouriaux, Frederic; Watier, Eric; Bertheuil, Nicolas
Abstract: Introduction: Many recent studies concerning autologous fat grafting in the eyelids have been published, mostly consisting of case reports and retrospective case series. However, no study on the overall complication or satisfaction rate associated with the various grafting techniques exists. We performed a comprehensive literature review to determine the outcomes and complications of eyelid fat grafting, as well as patient satisfaction. Methods: A systematic review of the literature using the PRISMA criteria was conducted. This protocol was registered at the Prospective Register of Systematic Reviews at the National Institute for Health Research. Results: Sixteen studies, representing 1, 159 patients and published between June 2004 and December 2014, were included. Satisfactory results, judged by clinical examination, were observed in all studies. Few postoperative complications were reported. Conclusions: We demonstrated that the procedures were easy to perform, and achieved satisfactory and sustainable results with few complications in both reconstructive and cosmetic surgery. However, a wide disparity exists in the various fat harvesting, fat purification, and reinjection techniques. Further studies are required to assess the long-term outcomes. Our conclusions should be accepted cautiously due to the small number of articles and the lack of evidence in published studies.